2020
DOI: 10.1089/acm.2020.0077
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Adverse Events and Associations with Stress Levels and the Practice of Yoga: Survey Findings from a Population-Based Study of Diverse Emerging Young Adults

Abstract: Objectives: This study examines the prevalence of exposure to adverse events and associations with stress levels among a diverse population-based sample of young people. The study further explores whether these vulnerable populations, who have the potential to benefit from the mind-body practice of yoga, engage in a regular yoga practice.Design: EAT 2018 (Eating and Activity over Time) is a population-based study in which survey data were collected from 1568 ethnically/racially diverse (81.2% nonwhite) emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
3
12
0
3
Order By: Relevance
“…When comparing the present results to the previous findings on MPBA interventions, it appears that other reviews support similar outcomes and positive impacts on mental and physical well-being/health [ 23 , 24 , 25 , 36 , 40 , 85 , 108 , 109 , 110 , 111 ]. In particular, yoga interventions lowered stress in college students.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…When comparing the present results to the previous findings on MPBA interventions, it appears that other reviews support similar outcomes and positive impacts on mental and physical well-being/health [ 23 , 24 , 25 , 36 , 40 , 85 , 108 , 109 , 110 , 111 ]. In particular, yoga interventions lowered stress in college students.…”
Section: Discussionsupporting
confidence: 78%
“…In a diverse 1568 young adult (mean age: 22.0 ± 2.0 years) population-based survey (Eating and Activity over Time) EAT 2018 study, researchers found a high prevalence (43.9%) of exposure to stress and adverse events. However, those who were exposed to adverse events, which were associated with higher stress levels, 12.7% of young adults reported either more or similarly likely to practice yoga, at least 30 min/week [ 111 ]. Further, in a systematic review of interventions aimed to reduce perceived stress in graduate nursing students, researchers found that self-care strategies were effective [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…This research is verified with the results obtained in [29], which stated that yoga improves memory and cognitive functions in the target subjects. Also, in this line, given the potential benefits of yoga for populations living with high stress, it is important to develop more outreach efforts and provide accessible, acceptable, and affordable opportunities for the practice of yoga [30]. First-person students reported that the practice of yoga improved social-emotional competence over time in relation to the control condition [31].…”
Section: Discussionmentioning
confidence: 99%
“…Key items from the EAT 2010 survey were retained on the follow‐up EAT 2018 survey, while additions were made to assess new areas of interest (Larson et al, 2013; Bucchianeri, Eisenberg, & Neumark‐Sztainer, 2013; Neumark‐Sztainer, Wall, Fulkerson, & Larson, 2013; Neumark‐Stzainer et al, 2020). Focus groups with 29 emerging adults were conducted to pretest the EAT 2018 survey.…”
Section: Methodsmentioning
confidence: 99%
“…Key items from the EAT 2010 survey were retained on the follow-up EAT 2018 survey, while additions were made to assess areas of emerging interest and to re ect participants' transition from adolescence to young adulthood (40,(44)(45)(46). Focus groups with 29 emerging adults were conducted to pretest the EAT 2018 survey.…”
Section: Survey Development and Variablesmentioning
confidence: 99%